2021
DOI: 10.1038/s41598-020-79742-9
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid-binding immunoglobulin-like lectin-15 expression on peritumoral macrophages is a favorable prognostic factor for primary central nervous system lymphoma patients

Abstract: Sialic acid-binding immunoglobulin-like lectin-15 (Siglec-15) is a new immune checkpoint molecule and its role of primary central nervous system lymphoma (PCNSL) tumor microenvironment has been unclear. We explored the Siglec-15 and programed death-ligand 1 (PD-L1) expression in tumor tissues and analyzed the association between the expression of these molecules and overall survival in newly diagnosed PCNSL. A total of 60 patients diagnosed with diffuse large B-cell lymphoma in PCNSL were included in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…21 Fubada et al have also demonstrated that the overexpression of Siglec-15 is indicative of a good prognosis for patients with primary central nervous system lymphoma. 22 Our ndings showed that Siglec-15 overexpression was related to an increase in the distant metastasis rate of NPC patients, which may be attributable to the fact that Siglec-15-mediated immune escape promotes the malignant biological behavior of tumor cells. Furthermore, our results showed that there was a negative correlation between the expression of Siglec-15 and PD-L1; hence, we further explored whether the combination of PD-L1 and Siglec-15 had an impact on the survival rate of NPC patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…21 Fubada et al have also demonstrated that the overexpression of Siglec-15 is indicative of a good prognosis for patients with primary central nervous system lymphoma. 22 Our ndings showed that Siglec-15 overexpression was related to an increase in the distant metastasis rate of NPC patients, which may be attributable to the fact that Siglec-15-mediated immune escape promotes the malignant biological behavior of tumor cells. Furthermore, our results showed that there was a negative correlation between the expression of Siglec-15 and PD-L1; hence, we further explored whether the combination of PD-L1 and Siglec-15 had an impact on the survival rate of NPC patients.…”
Section: Discussionmentioning
confidence: 70%
“…21 Fudaba et al have also shown that the detection of Siglec-15 in patients with primary CNS lymphoma was indicative of a good prognosis. 22 However, the relationship between Siglec-15 expression and NPC patient prognosis has not been identi ed in the current study.…”
Section: Introductionmentioning
confidence: 79%
“…Next to its expression on myeloid cells, Siglec-15 was observed on stromal cells and even on tumor cells (28). Siglec-15 expression on tumor cells was verified by others on several types of cancer, such as lymphoma, gastric cancer and acute myeloid leukemia (29)(30)(31). Similarly, Siglec-8 has been reported to be expressed by breast cancer cells (32).…”
Section: Siglec Expression Within the Tmementioning
confidence: 69%
“…More recently, high Siglec-15 was also found to promote osteosarcoma progression via the activation of the DUSP1/MAPK signaling pathway [152], and hepatocellular carcinoma migration via CD44 interaction, which prevented lysosomal degradation [153]. As Siglec-15 is mutually exclusive to PD-L1, it is now emerging as a novel immune inhibitor for anti-PD-1/PD-L1 resistant patients [154,155].…”
Section: Siglec-15mentioning
confidence: 99%